1989
DOI: 10.1002/hep.1840090415
|View full text |Cite
|
Sign up to set email alerts
|

The aminopyrine breath test predicts the outcome of hepatic transplantation in pigs

Abstract: The aminopyrine breath test has been performed on Day 1 and Day 7 in pigs following experimental liver allografting. The results show that at 24 hr after surgery there was a significant reduction in liver function in all animals as measured by the elimination rate constant of 14CO2 in the breath. This was very profound in the group that died within 5 days (0.09 +/- 0.01 hr-1) and was significantly different from the group that survived (0.16 +/- 0.01 hr-1). There appears to be a critical value of the eliminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Among these, some studies [25] showed that the ABT was able to predict the outcome of liver transplantation in the pig and to diagnose acute allograft rejection [26] better than other laboratory test in humans. Moreover, a decrease in cytochrome P450 activity was demonstrated after ischaemia in rats [27].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, some studies [25] showed that the ABT was able to predict the outcome of liver transplantation in the pig and to diagnose acute allograft rejection [26] better than other laboratory test in humans. Moreover, a decrease in cytochrome P450 activity was demonstrated after ischaemia in rats [27].…”
Section: Discussionmentioning
confidence: 99%
“…Such drug-metabolizing activity can be compromised after liver transplantation, and several studies sug-gest that it may serve as a good index of early graft function. [11][12][13] This may have an important impact on the health of the transplant recipient as evidenced, for instance, by an increased toxicity of immunosuppressants caused by decreased metabolism. 14 Alterations in the activity of the hepatic cytochrome P-450-dependent mono-oxygenase system would also be expected to perturb the metabolism of several other xenobiotics, as well as such endogenous substrates as bile acids and certain steroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that drug-metabolizing capacity is a suitable indicator of hepatic functional integrity after liver transplantation. [11][12][13] Observed disturbances in liver metabolic integrity after cold preservation may further result in clinically relevant disturbances in drug handling, as seen particularly for immunosuppressive therapy. 14 It is therefore important to improve cold storage conditions to maintain not only a proper hepatocellular viability, but also near-normal functions, such as cytochrome P-450-dependent drug metabolism.…”
Section: Copyright 1999 By the American Association For The Study Of mentioning
confidence: 99%
“…The functions of the liver can broadly be broken down into seven main areas: catabolic and anabolic functions with respect to carbohydrate, fat, and protein metabolism; production of bile; production and excretion of bilirubin; immunological functions involving the production and release of cytokines and interferons; scavenging and ®ltration of endotoxins and bacteria; storage of vitamin B 12 and glycogen; and the biotransformation and elimination of drugs and xenobiotics.…”
Section: Assessment Of Liver Function: Its Application To Outcome Fromentioning
confidence: 99%
“…11 Aminopyrine (assessed as the 14 CO 2 aminopyrine breath test) is also negligibly protein bound, and like antipyrine assesses hepatic metabolizing capacity rather than liver blood¯ow. Although it has been used in the pig to assess the outcome of transplantation, 12 the aminopyrine test has a number of limitations to its use in man. For instance, reduction in the test output can occur in patients with sepsis and viral infections; there is administration of radioactivity; endogenous carbon dioxide production may interfere with the results; and the drug can induce agranulocytosis in patients sensitized previously by pyrazolone derivatives.…”
Section: Capacity-limited Binding-insensitive Hepatic Eliminationmentioning
confidence: 99%